The SAGE Handbook of Qualitative Business and Management Research Methods: History and Traditions - Cassell, Catherine (SAGE Publications Ltd, 2018)
The SAGE Handbook of Qualitative Business and Management Research Methods provides a state-of - the art overview of qualitative research methods in the business and management field. Bringing together a team of leading international researchers, the chapters offer a comprehensive overview of the history and traditions that underpin qualitative research in the field. The chapters in this volume have been arranged into four thematic parts: Part One: Influential Traditions underpinning qualitative research: positivism, interpretivism, pragmatism, constructionism, critical, poststructuralism, hermeneutics, postcolonialism, critical realism, mixed methods, grounded theory, feminist and indigenous approaches. Part Two: Research Designs: ethnography, field research, action research, case studies, process and practice methodologies. Part Three: The Researcher: positionality, reflexivity, ethics, gender and intersectionality, writing from the body, and achieving critical distance. Part Four: Challenges: research design, access and departure, choosing participants, research across boundaries, writing for different audiences, ethics in international research, digital ethics, and publishing qualitative research.